ANALISIS TINGKAT AKURASI PENETAPAN NJOP PADA PAJAK BUMI DAN BANGUNAN TERHADAP NILAI PASAR DENGAN METODE ASSESSMENT SALES RATIO PADA BPPRD KOTA TANJUNGPINANG - Meidi Yanto (Bajang Institute, 2023)
The purpose of this study was to find out how the determination of NJOP on Land and Building Tax at the BPPRD Tanjungpinang and to find out the level of accuracy of the determination on market value using the sales ratio assessment method. This study uses a type of qualitative descriptive research, namely research that seeks to describe the current problem solving based on data presenting data, analyzing and interpreting. In order to provide a clear, logical and accurate picture of the results of data collection, the data obtained were collected in the form of data obtained through interviews, observation, documentation, and literature study which were then analyzed more deeply. The results showed that the determination of the NJOP of land and buildings for conditions on January 1 of the tax year was carried out through a land and or building appraisal process. Based on the ASR calculation, it is known that for the Tanjungpinang Timur District, the determination of NJOP based on the Assessment Sales Ratio when referring to the regulations of the Directorate General of Taxes and IAAO is not in accordance with market value. Simultaneously, re-appraisal of sub- districts with low ASR levels is needed, increasing synergy with related agencies, and improving land appraisal performance